2009
DOI: 10.1080/10426910902748032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post Heat-Treatment on Surface Characteristics and Adhesive Bonding Performance of Medium Density Fiberboard

Abstract: A series of commercially manufactured medium density fiberboard (MDF) panels were exposed to a post-manufacture heat-treatment at various temperatures and durations using a hot press and just enough pressure to ensure firm contact between the panel and the press platens. Postmanufacture heat-treatment improved surface roughness of the exterior MDF panels. Panels treated at 225 � C for 30 min had the smoothest surface while the roughest surface was found for the control panels. Wettability and the adhesive bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 19 publications
4
31
0
1
Order By: Relevance
“…the contour of the surface, has a significant effect on the distribution of the shear forces [39]. The results of the contact profilometry of this study are in line with the previously published literature, where similar tests have been conducted with other wood species treated with different heat treatment methodologies [40][41][42][43]. The mechanism of the heat treatment-induced decrease in roughness is not clear.…”
Section: Surface Profilometrysupporting
confidence: 85%
“…the contour of the surface, has a significant effect on the distribution of the shear forces [39]. The results of the contact profilometry of this study are in line with the previously published literature, where similar tests have been conducted with other wood species treated with different heat treatment methodologies [40][41][42][43]. The mechanism of the heat treatment-induced decrease in roughness is not clear.…”
Section: Surface Profilometrysupporting
confidence: 85%
“…All approaches presented had advantages and drawbacks. In general, the mechanical performance and bonding quality of treated plywood diminished after TM; the wooden surfaces exposed to high temperature might be subjected to surface inactivation with possible adhesion problems during its manufacturing (Ayrilmis and Winandy 2009). While the production of heat-treated poplar plywood is feasible, it needs important improvements to avoid reductions in mechanical properties (Goli et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In most of the cases, the adhesive bond performance of the wood is negatively affected by the higher temperature and higher treatment period [17,18]. However, some studies reported that a better bonding strength is achieved with lower heating treatment conditions which use lower temperature and duration [14,[19][20][21].…”
mentioning
confidence: 99%
“…The higher shear strength value was obtained for the plywood sample having a smoother surface at 52 °C. Ayrilmis et al [18] investigated the effect of heat treatment on adhesive bonding performance and concluded that the bonding strength of the heat-treated medium density fiberboard panels decreased with increasing contact angle even though the surface roughness improved. Surface wettability mechanism of material after heat treatment plays an important role for the bond performance [22][23][24][25].…”
mentioning
confidence: 99%